Climate change policies and strategies for central banks: Central Bank of Kenya and International Food Policy Research Institute sign a memorandum of understanding - Omune, Lensa; Mbuthia, Juneweenex (CGIAR System Organization, 2024)
Economies are exposed to myriads of external risks such as production variability from climate shocks, volatility in global commodity prices, fluctuations in foreign investments, among other risks. For instance, climate change, a key determinant of production variability, continues to dominate the global risk landscape posing a long-term threat to the global economy. As the severity, frequency and unpredictability of extreme weather events increase, uncertainty over availability of food, commodities, and labor increases, in turn, impacting investment, consumption and trade at a macro level.